[Fieldbook on the construction of a Blue Mountains railway] - Firth, Thomas Rhodes (1869)
Contains original diagrams and notes on the construction of a railway in the Blue Mountains, N.S.W.
Manuscript reference no.: NLA MS 170.
Keywords: Railroads -- New South Wales -- Blue Mountains -- Design and construction; Blue Mountains (N.S.W. : Mountains) -- History